Needs Analysis in Learning Media Development Based on Augmented Reality (AR) for Computer Network Installation Courses - Mubai, Akrimullah; Rukun, Kasman; Giatman, Giatman; Edidas, Edidas (Universitas Negeri Padang, 2020)
This needs analysis research consists of field studies and literature studies. Where the purpose of this research is; 1) description of student achievement values ​​and learning processes, 2) the uses and constraints faced by students in the use of learning media Computer Network Installation, 3) formulation of instructional media needed in learning computer network installation. This research belongs to the type of qualitative descriptive research. The subjects of this study were 29 students of Informatics Engineering Education study programs and 2 lecturers of computer network installation courses. Data obtained using a questionnaire and analysis qualitatively through stages; arranging, tabulating, analyzing qualitative data and making interpretations of the results of the analysis according to the problems and objectives of the study which then makes conclusions. The results showed that; 1) there are still many students who have not reached the score above the minimum criteria and fail in carrying out the practicum process, 2) the biggest obstacle faced by students in implementing Computer Network Installation learning is the limitations of using instructional media that are less effective to support independent learning, 3) the media that need developed for learning Computer Network Installation which is learning media based on Augmented Reality (AR).